Reduction in the development of coffee orange rust with homeopathic mixture - Rodríguez Hernández, Cesáreo; Ramos-Reyes, Sandra; Escamilla-Prado, Esteban; Ruiz-Espinoza, Felipe de Jesús (Revista Mexicana de Ciencias Agrícolas, 2019)
Orange rust (Hemileia vastatrix Berk. & Broome) is the main disease of coffee cultivation, and given the need to reduce the losses it causes, ecological alternatives have been implemented for its control and under this concept this research aimed to quantify the effect of four homeopathic preparations and 0.5% Bordeaux mixture in the severity, foliar infestation and defoliation caused by this fungus, the experiment was carried out in the East Regional Center of the Autonomous University Chapingo in Huatusco, Veracruz, Mexico, from September to November of 2014, where the homeopathic plants were sprayed every week for 60 d, with four repetitions/trees per treatment in a randomized complete block design. The Bordeaux mixture at 0.5% was applied twice for 60 days and the control trees were not applied. At 60 d the severity was recorded in 10 leaves per tree and at 30 and 60 d the foliar infestation and defoliation were quantified. The results showed that the severity was not affected at 60 d or the foliar infestation at 30 d, the plant polypharm (mixture of 72 anti-stress homeopathic preparations and diseases, nutrients, pests and plants of agricultural importance)/212 Centesimal Hahnemanniana, 49.75% decreased the defoliation at 30 d and the homoeopathic mixture reduced 26.65 and 45.06% foliar infestation and defoliation at 60 d. The homeopathic mixture allows to protect the plant rather than to manage or eliminate the pathogen, it is an ecological and organic alternative to solve the current contingency of coffee rust.